PERANAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS SUMBER DAYA MANUSIA DAN PERSPEKTIF KEBERHASILAN PENERAPAN ERP PADA PT TELKOM INDONESIA - Rulis Setyowati; Hwihanus Hwihanus (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
Enterprise Resource Planning (ERP) systems integrate all organizational functions, integrating inventory management, manufacturing, finance, human resources and accounting into one system. modular ERP systems for businesses can afford any module to suit their specific needs. ERP enables sharing of information between various business functions and improves communication with external parties. One use of the system is called "Enterprise Resource Planning," or ERP. Accounting information in business, and adopted in PT Telkom Indonesia because businesses have to comply with international standards and because it is their job. Best practices, best procedures, and best features in software are sold, costed, and written. In order to achieve the benefits of a more efficient framework that is interconnected and adaptable, this mini-study will examine the views of PT Telkom Indonesia's ERP installation success and make savings and staff reductions. PT Telkom Indonesia has the ability to predict and assess the future of consumers. The level of training and professional experience of the team shows their professionalism.